Analisis Penggunaan Aplikasi Keuangan & Kontrol Diri Terhadap Literasi Keuangan Mahasiswa - Afriana Afriana; Asriany Asriany; Sari Ratna Dewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to empirically analyze the effect of financial application usage and self-control on the financial literacy of students at Muhammadiyah University Palopo. The main objective of this study is to determine the extent to which the use of financial technology (financial applications) and students' level of self-control contribute to improving personal financial management skills. The approach used is a quantitative method with a survey technique. The research population consisted of 180 active fifth-semester students, and 64 respondents were selected as samples using probability sampling with the simple random sampling method. Data were collected through an online questionnaire and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that both the use of financial applications and self-control had a significant effect on students' financial literacy, both partially and simultaneously. The self-control variable had a more dominant influence than the use of financial applications, with a joint contribution value (R²) of 50.2%. These findings indicate that students' financial literacy is not only determined by their ability to utilize financial technology but also by internal factors such as their ability to control themselves in managing finances. The results of this study are expected to serve as a basis for educational institutions to strengthen digital-based financial education programs and the formation of students' financial character.